Acetylation of the histone-like protein HBsu at specific sites alters gene expression during sporulation in Bacillus subtilis - Popova, Liya; Pandey, Hritisha; Schreiber, Olivia R.; Papachristou, Charalampos; Carabetta, Valerie J. (Frontiers in Microbiology, 2025)
IntroductionSporulation is an adaptive response to starvation in bacteria that consists of a series of developmental changes in cellular morphology and physiology, leading to the formation of a highly resistant endospore. In Bacillus subtilis, there is an intricate developmental program which involves the precise coordination of gene expression and ongoing morphological changes to yield the mature spore. The histone-like protein HBsu is involved in proper spore packaging and compaction of the chromosomal DNA.MethodsPreviously, we found that the acetylation of different lysine residues on HBsu impairs sporulation frequency and spore resistance properties. One mechanism by which HBsu influences the process of sporulation could be through the regulation of gene expression. To test this idea, we performed RT-qPCR to analyze gene expression throughout the sporulation process in wildtype and seven acetylation-mimicking (lysine to glutamine substitutions) mutant strains.ResultsAcetylation of HBsu at K41 increased the expression of key early and late sporulation genes, especially during the later stages. For example, overexpression σF and σG drive expression of their regulon members at inappropriate times. The gene expression profiles for the acetyl-mimic mutants at K3, K37, K75, K80, and K86 were largely unchanged, but did have reductions of key late sporulation proteins, which could explain the observed defects in spore resistance properties.DiscussionThese findings suggest that K41 acetylation activates gene expression and might represent an “on–off” switch for important regulatory factors as cells transition from early to late phases. We propose that the acetylation of HBsu at specific sites regulates gene expression during sporulation and this is required for proper timing and coordination.